2020
DOI: 10.1002/smtd.201900733
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Doping Effect on Mn3O4 Nanoparticles for Electrochemical Water Oxidation under Neutral Condition

Abstract: As the demand for energy has dramatically increased in the past decade, electrochemical water splitting has been regarded as an attractive approach to produce renewable hydrogen energy. However, large overpotentials of oxygen‐evolving reaction (OER) is a key bottleneck for practical application. Thus, water‐oxidizing electrocatalysts with low cost and high efficiency should be developed. Here, 5 nm‐sized Mn3O4 nanoparticles (NPs) are synthesized by a hydrothermal method, which is appropriate for large‐scale pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 44 publications
(70 reference statements)
0
30
0
Order By: Relevance
“…17) and Mn 3 O 4 (ref. 18)) with unique electroactive redox pairs and good corrosion resistance in an alkaline environment have been confirmed as excellent OER electrocatalysts. 19 Moreover, the electrocatalytic performance of the spinel oxide can be further improved by element doping to tune the electronic structure and enhance conductivity.…”
Section: Introductionmentioning
confidence: 89%
“…17) and Mn 3 O 4 (ref. 18)) with unique electroactive redox pairs and good corrosion resistance in an alkaline environment have been confirmed as excellent OER electrocatalysts. 19 Moreover, the electrocatalytic performance of the spinel oxide can be further improved by element doping to tune the electronic structure and enhance conductivity.…”
Section: Introductionmentioning
confidence: 89%
“…1e-h). The SEM results showed that the surface of Fe 200), ( 103), ( 211), ( 004), ( 220), ( 105), (321), ( 224) and (400), respectively , [41]. The illustration in Fig.…”
Section: Characterization Of As-prepared Samplesmentioning
confidence: 95%
“…[13][14][15][16] Among the multitudinous electrode materials investigated to date, manganese oxides, as a result of their numerous advantages such as low cost, low toxicity, abundant resources and rich redox state in particular, are extremely attractive. [17][18][19][20][21] It has been reported that Mn cations with Mn 3+ valence manifest optimum catalytic activity towards the OER. 19,20,22,23 Mn 3 O 4 can effectively catalyze the OER in alkaline media due to its variable valence state and coordination structure.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] It has been reported that Mn cations with Mn 3+ valence manifest optimum catalytic activity towards the OER. 19,20,22,23 Mn 3 O 4 can effectively catalyze the OER in alkaline media due to its variable valence state and coordination structure. 22,23 Nevertheless, the principal problems are that pure Mn 3 O 4 has poor conductivity (10 −7 -10 −8 S cm −1 ) and small specific surface area as well as significant agglomeration, 18,24,25 which will expose few active sites, resulting in inferior catalytic performance.…”
Section: Introductionmentioning
confidence: 99%